EarthComm-Supported Geospatial Inquiry Improves Analytical Thinking in Disaster-Focused Geography Learning - Rivela Dwi Kharisma Putri; Alfi Sahrina (CV Bumi Spasial, 2026)
In contemporary learning, students are encouraged to develop critical, analytical, and reflective thinking skills as well as the ability to express ideas creatively and systematically. One learning approach that supports these objectives is the EarthComm learning model, which emphasizes problem based learning by engaging students directly with real world environmental issues. Through this approach, students actively analyze problems, interpret data, and propose solutions, thereby fostering higher order thinking skills. This study aimed to examine the effect of the EarthComm learning model on students’ analytical thinking skills in senior high school geography learning. The research employed a quasi experimental design using a post test only control group. The participants were Grade XI social science students at SMA Negeri Tempeh, divided into an experimental group and a control group. The learning intervention was implemented over four weeks, consisting of three instructional meetings lasting three times forty five minutes based on the EarthComm learning syntax, followed by one week for group project completion and post test administration. Data were collected using descriptive test instruments that had been tested for validity and reliability. Prior to hypothesis testing, prerequisite analyses were conducted, including normality and homogeneity tests. Post test scores from both groups were analyzed using an independent samples t test. The results showed a significant difference in analytical thinking skills. The experimental group achieved a higher mean score than the control group. These findings demonstrate that the EarthComm learning model is effective in improving students’ analytical thinking skills in geography education.